A Longitudinal Cohort Study of Student Motivational Factors Related to Academic Success and Retention Using the College Student Inventory. (November 2015) - Slanger, William D.; Berg, Emily A.; Fisk, Paul S.; Hanson, Mark G.
Ten years of College Student Inventory (CSI) data from one Midwestern public land-grant university were used to study the role of motivational factors in predicting academic success and college student retention. Academic success was defined as cumulative grade point average (GPA), cumulative course load capacity (i.e., the number of credits earned divided by number of classes for which a grade was given), cumulative ratio of credits earned to credits taken, and retention to subsequent fall semesters through eight semesters of study. An aggregation of 256 stepwise linear regression results showed Predicted Academic Difficulty and Dropout Proneness were predictive of cumulative GPA across all cohort groups and through the eighth semester of study. Three of the four CSI compound scales (not Receptivity to Institutional Help) were found to be predictive of ratio of credits earned to credits attempted through the fourth semester and retention through a maximum of eight semesters. In addition to drawing light to sophisticated nuances with which the CSI can be practically applied to individual students, this study suggests that the CSI can play a global role in monitoring over time changing student motivational factors related to college student success.